Factors Which Affect of Masticatory Muscle Cross-sections in Complete Denture Wearers - Tanabe, Tadaki (Nihon Hotetsu Shika Gakkai Zasshi, 1995)
Many authors attempt to calculate muscle force per unit of cross-section of jaw muscles. However, nothing is known in regard to reduction of the size of jaw muscles in elderly edentulous patients. The purpose of this study was to determine whether or not tooth loss and aging affect the reduction of the jaw muscle cross-section in elderly edentulous patients. Thirty-three selected subjects were 11 young dentate, 11 elderly dentate and 11 elderly edentulous who were the same age as elderly dentate, and magnetic resonance imaging, cephalometric radiography through EMG pattern was used in relation to facial morphology. There was a significant reduction of the cross-sectional area in the edentulous group, and EMG activity showed a significant reduction in the elderly dentate and especially edentulous groups. The study showed a correlation between cross-sectional area and EMG activity. However, only the edentulous group showed no correlation concerning the posterior temporal muscle. Tooth loss may affects a reduction in the cross-section of masticatory muscle. Both tooth loss and aging may affect muscle activity in relation to facial morphology.